Weathering the storm: School funding in the COVID-19 era. (September 2020) - Baker, Bruce D.; Weber, Mark; Atchison, Drew
The COVID-19 pandemic is creating a crisis in state and local budgets, potentially leaving many schools to face budgetary declines even as they've had to transform the way they serve their students, particularly those who are most vulnerable. Bruce Baker, Mark Weber, and Drew Atchison offer four recommendations for mitigating the looming fiscal crisis. 1) Provide a robust federal aid package; 2) Consider tax increases; 3) Distribute state aid equitably; and 4) Cancel aid programs that favor affluent districts .